2022
DOI: 10.3847/psj/ac7f34
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Rotational Characterization of the Didymos System prior to the DART Impact*

Abstract: The smallest member of the Didymos binary near-Earth object system (Dimorphos) is the target of the DART/LICIACube mission, the first attempt to change the orbit of another celestial body via a kinetic impactor. It is important to characterize the unperturbed system prior to the DART impact. In this work we obtained, for the first time, spectral characterization of the system at several rotational phases from TNG+DOLORES in the visible range (0.34–0.81 μm). This is crucial in order to disentangle the primary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Variation of the reflectance spectra of the Didymos system might occur due to a color variation on Didymos's surface, regardless of the DART impact. Ieva et al (2022) reported a slope variation at the visible wavelength range, observed before the impact (on 2021 February). However, they could not correlate this variation with Didymos's rotation phases.…”
Section: Spectral Slope Variationmentioning
confidence: 97%
“…Variation of the reflectance spectra of the Didymos system might occur due to a color variation on Didymos's surface, regardless of the DART impact. Ieva et al (2022) reported a slope variation at the visible wavelength range, observed before the impact (on 2021 February). However, they could not correlate this variation with Didymos's rotation phases.…”
Section: Spectral Slope Variationmentioning
confidence: 97%
“…The mission targeted the secondary asteroid in an eclipsing binary system because the experiment could use a single impacting spacecraft and measure the change in the orbit of the secondary through ground-based observations. The Didymos system was selected as the target because it is among the most accessible (low Δ V ) of the near-Earth binaries, it has been extremely well characterized 4 6 , 8 12 and Dimorphos is in the size range identified as relevant for deflection by a kinetic impactor 13 , 14 .…”
Section: Mainmentioning
confidence: 99%
“…Spectra indicate the presence heterogeneity of surface materials on Didymos, with various concentrations of probably hypersthene with a grain radius a < 25 μm, and olivine with a grain radius a < 45 μm (ref. 22 ). Laboratory simulations of space weathering showed that irradiation can cause significant reddening of olivine’s reflectance spectrum 23 .…”
Section: Mainmentioning
confidence: 99%